Necrose gordurosa subcutânea do recém-nascido: relato de caso e revisão de literatura - Júlia Belcavelo Contin Silva; Bruno Augusto Alvares; João César Lyra; Alice Yamashita Prearo; Maria Regina Bentlin; Silvio Alencar Marques (Sociedade Brasileira de Pediatria, 2023)
INTRODUCTION: incomplete. RESULTS: Fatty necrosis of the subcutaneous tissue is an uncommon inflammation, with a still unknown pathogenesis, which appears in newborns in the first weeks of life. The lesions are characterized by areas of edema and erythema that progress to hardened and painless subcutaneous plaques or nodules. The risk factors for this panniculitis are hypoxia and perinatal stress, such as traumatic or prolonged delivery and, more recently, therapeutic hypothermia. The diagnosis is clinical, the evolution is self-limited and benign, but the level of serum calcium should be monitored, as hypercalcemia can occur, leading to severe symptoms. In our report, we describe a case of subcutaneous adipose necrosis associated with prolonged expulsive and therapeutic hypothermia. CONCLUSION: Although infrequent, early recognition of this condition, especially in newborns with risk factors, is important, and can guide clinical follow-up including monitoring calcium, pain control and not using antibiotics.